STUDENTS’ ACCEPTANCE IN USING IPAD FOR MEANINGFUL LEARNING EXPERIENCE: A PRELIMINARY ANALYSIS - Shaarani, Ahmad Shaarizan; Bakar, Norasiken; Abdullah, Aida Nasirah; Abd Aziz, Maslita; Saifudin, Wan Sazli Nasaruddin (Journal of Human Capital Development (JHCD), 2016)
Nowadays learning has become more essential towards human beings. The ways of learning changes across the years as the technology grows. Tablet has become one of the most important items that every student should have. Students prefer to bring their tablet to classroom rather than bringing their laptop. This is due to the light weight of the tablet itself. One of the most famous tablets is the iPad. The aim of this paper is to conduct a study based preliminary analysis for the students’ acceptance in meaningful learning using iPad. In this preliminary study, a set of online questionnaire as distributed to 106 diploma students and 84 degree students from the Faculty of Information and Communication Technology (FTMK) of Universiti Teknikal Malaysia Melaka (UTeM). This paper shares the preliminary findings on the perceptions of the students on the use of iPad in the learning and teaching process. All the collected data has been analysed using the pie chart. The results show that most of the students have agree that use of iPad enhance their learning experience. Keywords: engaging, using iPad, iBook, acceptance, meaningful learning, flipped learning